Julie Hruby and Debra Trusty (eds). From Cooking Vessels to Cultural Practices in the Late Bronze Age Aegean. - Dickinson , Oliver (Journal of Greek Archaeology, 2018)
This book had its origin in a panel held at the 11th Annual Meeting of the Archaeological Institute of America in January 2014; the papers given there, suitably adapted for publication, have been added to by contributions from scholars working on comparable material. All chapters are substantial, and apart from the short introduction and finale all are illustrated with a range of photographs, drawings, tables and sometimes thin-sections. It is well-presented, with a colourful cover showing, on the front, modern replicas of Minoan-style cooking pots, made by Jerolyn Morrison, one of the contributors to this book, in use.